CXC chemokine ligand‐10 promotes the accumulation of monocyte‐like myeloid‐derived suppressor cells by activating p38 MAPK signaling under tumor conditions. Issue 1 (3rd November 2022) - Sun, Yingying; Mo, Yan; Jiang, Shu; Shang, Chao; Feng, Yunpeng; Zeng, Xianlu
Abstract: CXC chemokine ligand‐10 (CXCL10) is a small (10 kDa) secretory protein in the CXC subfamily of cytokines. CXCL10 has been reported to play an important role in antitumor immunity as a chemotactic factor. Tumor development is always accompanied by the formation of an immunosuppressive tumor microenvironment, and the role of CXCL10 in tumor immunosuppression remains unclear. Here, we reported that CXCL10 expression was significantly upregulated in mice with melanoma, and tumor cells secreted large amounts of CXCL10. Myeloid‐derived suppressor cells (MDSCs) are an important part of the immunosuppressive tumor microenvironment. Our results showed that CXCL10 promoted the proliferation of monocyte‐like (mo)‐MDSCs by activating the p38 MAPK signaling pathway through CXCR3, which led to the abnormal accumulation of mo‐MDSCs under tumor conditions. This finding provides a new understanding of the mechanism by which a tumor‐induced immunosuppressive microenvironment forms and suggests that CXCL10 could be a potential intervention target for slowing tumor progression. Abstract : This manuscript is based on the role of CXCL10 in tumor immunosuppression. Our results showed that CXCL10 promoted the proliferation of monocyte‐like (mo)‐MDSCs by activating the p38 mitogen‐activated protein kinase (MAPK) signaling pathway via CXCR3, which led to the abnormal accumulation of mo‐MDSCs under tumor conditions.